Production of Λ and ΛΛ correlations in the hadronic decays of the Z0 - Abreu, P; Adam, W; Adye, T; Agasi, E; Aleksan, R; Alekseev, G; Algeri, A; Allen, P; Almehed, S; Alvsvaag, S; Amaldi, U; Andreazza, A; et al. (1993)
An analysis of the production of the Λ baryon in the hadronic decays of the Z0 is presented, based on about 993K multihadronic events collected by the DELPHI detector at LEP during 1991 and 1992. The differencial cross section of the Λ and the correlations between Λ and Λ produced in the same event are compared to current models, based both on string fragmentation and on cluster decay. The predictions of the string fragmentation model are found to give satisfactory agreements with the data, clearly better than those of the cluster model. © 1993.